## Simplifying (2−7m 6 ) 2

This expression involves simplifying a binomial raised to the power of 2. We can achieve this using the **square of a binomial** formula:

** (a - b) 2 = a 2 - 2ab + b 2 **

Let's break down the expression:

**a = 2****b = 7m 6**

Now, let's substitute these values into the formula:

(2 - 7m 6 ) 2 = 2 2 - 2(2)(7m 6 ) + (7m 6 ) 2

Simplifying each term:

- 2 2 = 4
- 2(2)(7m 6 ) = 28m 6
- (7m 6 ) 2 = 49m 12

Putting it all together:

(2 - 7m 6 ) 2 = **4 - 28m 6 + 49m 12**

Therefore, the simplified form of (2−7m 6 ) 2 is **4 - 28m 6 + 49m 12**.